Japanese EFL Teachers' Perceptions of Communicative, Audiolingual and Yakudoku Activities - Gorsuch, Greta (Education Policy Analysis Archives, 2001)
In recent years, the learning of English as a Foreign Language in Japanese high schools has become the focus of new educational policies applied at the national level. One of these is The Course of Study issue by the Ministry of Education, in which teachers are, for the first time in a long series of curriculum guidelines, adjured to develop students' "positive attitudes towards communicating in English." Another is the JET program, which has put thousands of native English speaking assistant language teachers (ALTs) into Japanese secondary classrooms for the purpose of team teaching with Japanese teachers. Data resulting from a survey project of 876 Japanese high school English teachers was used to provide empirical evidence of teachers' levels of approval of communicative, audiolingual and traditional (yakudoku) activities. Teachers were also asked to rate the strengths of a variety of influences on their instruction, including university entrance exams, and pre- and in-service teacher education programs. Teachers' perceptions of both activities and instructional influences were examined in light of teachers' length of career, type of school (private versus public, academic versus vocational), and level of contact with an ALT. The data revealed the complexities of imposing broad, national educational policies on a diverse group of teachers, and in an educational culture which likely precludes teachers' use of communicative activities.